Case study: use of sentence completion with a person with aphasia and apraxia of speech. - Van Sickle, Angela; Dembowski, James (Clinical Linguistics & Phonetics, 2023)
Several interventions for acquired apraxia of speech (AOS) involve models, imitation, or repetition to elicit production of words. Early researchers wrote about anecdotal experiences, in which sentence completion facilitated speech production for individuals with AOS. The use of sentence completion to elicit production of words during intervention has not been systematically researched. The purpose of this research was to evaluate the effectiveness of sentence completion to elicit correct productions of words, as part of an intervention for one individual with aphasia and AOS. Training occurred three times a week for six weeks. In each session, the participant answered 20 simple questions, for which the answer was one of 20 target words. Ten of these 20 words were used for training, while the other set of 10 words remained untrained. During training, the participant produced words, as the final word of a sentence. The participant improved production of the trained target words. By the end of training, the participant produced more words, as the final word in a sentence and as the answer to a simple question. For this case study, an individual with severe Broca's aphasia and severe AOS increased the number of personally-relevant words produced following training using sentence completion to elicit production.